2020
DOI: 10.1177/1524838020977161
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Childbirth Experiences of New Parents: A Meta-Synthesis

Abstract: Childbirth is usually a joyous occasion. However, a significant proportion of parents experienced traumatic childbirths and suffered post-traumatic consequences, which needs urgent attention. Therefore, this review aimed to explore and understand the traumatic childbirth experiences of parents. A systematic review of qualitative studies was done. The consolidated evidence was meta-summarized and meta-synthesized based on Sandelowski and Barroso’s approach for synthesizing qualitative research. Seven electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
4
21
0
Order By: Relevance
“…Additionally, research indicated that the positive relationship between women and health care providers is crucial in creating a sense of control, providing women with safe and supportive birthing environments, and in uencing childbirth outcomes 38 . On the contrary, prior studies showed that most women shared their experiences of medical staff betraying their trust, neglecting them, and being apathetic and dismissive [14]. Such behaviors of medical staff contributed extensively to women's childbirth trauma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, research indicated that the positive relationship between women and health care providers is crucial in creating a sense of control, providing women with safe and supportive birthing environments, and in uencing childbirth outcomes 38 . On the contrary, prior studies showed that most women shared their experiences of medical staff betraying their trust, neglecting them, and being apathetic and dismissive [14]. Such behaviors of medical staff contributed extensively to women's childbirth trauma.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the women who had experienced negative traumatic births might avoid subsequent pregnancies, affecting their future fertility choices 14,18 . Given the importance of psychological birth trauma to women, exploring how to prevent women's psychological birth trauma is crucial to promote positive birthing experiences and reduce the negative consequences of childbirth in women 14 . However, there is scant evidence on prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Women's perception of psychological birth trauma is highly subjective (Taghizadeh et al, 2014). Each birth experience is unique to every woman, indeed, even the same events that occur during birth are perceived differently by every woman (Shorey and Wong, 2022). Studies showed that childbirth that appears normal and straightforward to healthcare professionals and is medically uneventful can be perceived as traumatic by the woman (Holopainen et al, 2020;Leinweber et al, 2022).…”
Section: Women's Subjective Feelingmentioning
confidence: 99%
“…Childbirth, a major event in a woman's life, is of a profound and complex nature (Shorey and Wong, 2022). Not only does it involve huge physical changes, but it is also accompanied by significant psychological fluctuations (Fenech and Thomson, 2015;Shorey and Wong, 2022). Negative birth experiences can even cause terrible psychological trauma to women (Fenech and Thomson, 2015;Shorey and Wong, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation